An Indonesian Secondary English Teacher’ Strategies to Accommodate Computer Mediated Communication for Group Discussions: An Interview Study - Oktaviani, Nadhifa Dwi; Sadiq, Nizamuddin (English Education Department, Universitas Islam Indonesia, 2023)
Numerous scholarly inquiries have been dedicated to exploring the advantageous consequences of implementing computer-mediated communication (CMC) for the purpose of orchestrating online group discussions. However, there is a paucity of empirical evidence elucidating how educators adapt to the use of CMC in the context of online group deliberations. The present research delves into the experiences of an English teacher in an Indonesian secondary school who employed CMC as a pedagogical tool. Grounded within the qualitative research paradigm, this study conducted unstructured in-depth interviews and subsequently subjected the interview transcripts to thematic analysis. The resultant findings shed light on several pivotal aspects of the teacher's role in CMC-enhanced online group discussions, which encompass the activation of students' creative faculties, the fostering of students' self-regulation of learning, the cultivation of a conducive learning environment, the advocacy for technological integration, and the effective management of assessment procedures in the online group discussion setting. Conclusively, this research posits that the incorporation of computer-mediated communication in online group discussions bears substantial educational advantages, as it affords students with alternative avenues to harness their skills and technology, thereby facilitating interpersonal exchanges among students and between students and educators.